Interaction of an annexin V homodimer (Diannexin) with phosphatidylserine on cell surfaces and consequent antithrombotic activity - Kuypers, Frans A.; Larkin, Sandra K.; Emeis, Jef J.; Allison, Anthony C. (Thrombosis and Haemostasis, 2007)
Annexin V(AV), a protein with anticoagulant activity, exerts antithrombotic activity by binding to phosphatidylserine (PS), inhibiting activation of serine proteases important in blood coagulation. The potential use of this protein as an anticoagulant is limited as it rapidly passes from the blood into the kidneys due to its relatively small size (36 kDa). We used recombinant DNA technology to produce a homodimer of human AV (DAV, 73 kDa), which exceeds the renal filtration threshold, and has a 6.5-hour half-life in the rat circulation. Human red blood cells with externalized PS were used to show that DAV had a higher affinity for PS-exposing cells than AV. DAV labeling sensitively identifies PS-exposing cells, was found to be a potent inhibitor of the activity of the prothombinase complexes and inhibits the ability of secretory phospholipase A2 to hydrolyze phospholipids of PS-exposing cells, reducing the formation of mediators of blood coagulation and reperfusion injury. DAV exerts dose-dependent antithrombotic activity in ratveins. This combination of activities suggests that DAV is a valuable probe to measure PS exposure and may be efficacious as a novel drug in a wide range of clinical situations.
Keywords: Phospholipids; annexins; haemostasis